CoMn2O4 embedded in MnOOH nanorods as a bifunctional catalyst for oxygen reduction and oxygen evolution reactions. Issue 32 (4th April 2018) - Wang, Ying; Hu, Tianjun; Liu, Qing; Zhang, Limin
Abstract : CoMn2 O4 embedded in MnOOH nanorods (CoMn2 O4 –MnOOH NRs) was prepared using a two-step hydrothermal method involving the oxidation of Mn by Co species in preformed MnOOH NRs, and the as-prepared catalyst exhibits an expectably remarkable performance for the ORR and the OER. Abstract : CoMn2 O4 embedded in MnOOH nanorods (CoMn2 O4 –MnOOH NRs) was prepared using a two-step hydrothermal method involving the oxidation of Mn by Co species in preformed MnOOH NRs. The as-prepared CoMn2 O4 –MnOOH NRs exhibit an expectably remarkable performance for the ORR and the OER, indicating their great potential for widespread application in fuel cells and metal–air batteries.